Evaluation of surgical therapy in advanced thymic tumors - Markowiak, Till Marvin; Ansari, Mohammed Khalid Afeen; Neu, Reiner; Schalke, Berthold; Marx, Alexander; Hofmann, Hans-Stefan; Ried, Michael (Cancers, 2021)
A complete resection of thymic tumors is known to be the most important prognostic factor, but it is often difficult to perform, especially in advanced stages. In this study, 73 patients with advanced thymic tumors of UICC stages III and IV who underwent radical resection were examined retrospectively. The primary endpoint was defined as the postoperative resection status. Secondary endpoints included postoperative morbidity, mortality, recurrence/progression-free, and overall survival. In total, 31.5% of patients were assigned to stage IIIa, 9.6% to stage IIIb, 47.9% to stage IVa, and 11% to stage IVb. In stages III a R0 resection was achieved in 53.3% of patients. In stages IV a R0/R1 resection was documented in 76.7% of patients. Surgical revision was necessary in 17.8% of patients. In-hospital mortality was 2.7%. Median recurrence/progression-free interval was 43 months (p = 0.19) with an overall survival of 79 months. The 5-year survival rate was 61.3%, respectively. Median survival after R2 resection was 25 months, significantly shorter than after R0 or R1 resection (115 months; p = 0.004). Advanced thymic tumors can be resected with an acceptable risk of complications and low mortality. In stage III as well as in stage IV the promising survival rates are dependent on the resection-status.
Gesehen am 12.11.2021